Endogenous Ciliary Neurotrophic Factor Protects GABAergic, But Not Cholinergic, Septohippocam pal Neurons Following Fimbria‐fornix Transection - Naumann, Thomas (Brain Pathol, 2006)
Application of neurotrophic proteins including ciliary neurotrophic factor (CNTF) and leukemia inhibitory factor (LIF), members of the family of gp130‐associated cytokines, can rescue CNS neurons from injury‐induced degeneration. However, it is not clear so far if these effects reflect a physiological function of the endogenous cytokines. Using fimbria‐fornix transection as a model, we examined whether responses of GABAergic and cholinergic septohippocampal neurons to axotomy are altered in mice lacking CNTF. In addition, we studied the cellular expression of CNTF, LIF and related cytokine receptor components in the septal complex following lesion. Degeneration of septohippocampal GABAergic neurons in the medial septum as indicated by the loss of parvalbumin‐immunoreactive neurons was accelerated and permanently enhanced in CNTF' mice as compared to wild‐type animals. Unexpectedly, the number of axotomized cholinergic MS neurons was significantly higher in CNTF‐deficient mice during the first 2 weeks postlesion. Both in wild‐type and in CNTF(‐/‐) mutants, expression of mRNAfor the CNTF‐specific α‐subunit of the cytokine receptor complex was specifically upregulated in axotomized GABAergic septal neurons, whereas enhanced expression of the LIF‐binding β‐subunit was specifically observed in axotomized cholinergic neurons. Following lesion, CNTF expression in wild‐type mice was induced in activated astrocytes surrounding the axotomized neurons and at the lesion site. Expression of LIF mRNA was localized in the GABAergic and cholinergic septohippocampal neurons. These results strongly indicate that endogenous CNTF, supplied by reactive glia cells, acts as a neuroprotective factor for axotomized CNS neurons. In the septum, endogenous CNTF specifically supports lesioned GABAergic projection neurons, whereas LIF may play a similar role for the cholinergic counterparts.